The association between hormonal variation, antioxidant status and oxidative stress in Iraqi women with endometriosis - Naji, Tamara S.; Al- Rubae’I, Salwa H. N.; Turki, Kisma M. (Journal of the Faculty of Medicine Baghdad, 2016)
Background: In the last years, Endometriosis affects up to 10 percent of reproductive aged Iraqi women. Little is known about the etiology of endometriosis in Iraqi women.Objectives: The aim of this study is to investigate the hormonal changes, antioxidant status, Coenzyme Q10 and oxidative stress in women patients with endometriosis.Patients and methods: 30 endometriotic women mean aged (31.16±5.61 year ) who were undergoing laparoscopy to participate in this study, and (n=30) healthy women volunteers mean aged (31.96±5.42 year) as control group.Results: The results in this study revealed a highly significant increased (P